2021
DOI: 10.37201/req/121.2020
|View full text |Cite
|
Sign up to set email alerts
|

Patients with non-tuberculous mycobacteria in respiratory samples: a 5-year epidemiological study

Abstract: Background. This study describes the characteristics of patients with positive cultures of non-tuberculous mycobacteria (NTM) in respiratory samples and determines the risk factors that predispose for a reinfection with different NTM species. Methods. Patients with NTM isolates in respiratory samples between 2013 and 2017 were studied. Additionally, risk factors and comorbidities of reinfected patients were analyzed. Results. The study was focused on the 280 patients with NTM isolation (28 were reinfected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…Previous studies have revealed that in most cases, several factors such as the existence of a pulmonary diseases or immunosuppression promote infections by NTM [ 19 ]. In this study, chronic bronchitis was the most frequent comorbidity in these patients, in contrast to the studies conducted by Matesanz et al which revealed that chronic obstructive pulmonary disease was the most frequent comorbidity in patients infected with NTM [ 20 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies have revealed that in most cases, several factors such as the existence of a pulmonary diseases or immunosuppression promote infections by NTM [ 19 ]. In this study, chronic bronchitis was the most frequent comorbidity in these patients, in contrast to the studies conducted by Matesanz et al which revealed that chronic obstructive pulmonary disease was the most frequent comorbidity in patients infected with NTM [ 20 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Mycobacterial infections are globally increasing despite the decline of tuberculosis [ 1 ]. Tuberculosis-causing bacteria include M. tb and Mycobacterium leprae resulting in tuberculosis and leprosy, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, around 6.6% of the US population or 16.4 million US individuals suffer from COPD. Patients with a history of lung disease such as COPD have an increased risk of Mycobacterium avium Complex (MAC) colonization [ 1 , 2 ]. In patients with COPD, the risk of contracting a mycobacterial infection is 15 times higher than that of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with preexisting respiratory conditions have greater susceptibility to infection. Lung disease, such as chronic obstructive pulmonary disease (COPD), contributes to increased risk of MAC colonization [ 12 , 13 ]. COPD is an inflammatory condition that leads to the obstruction of airflow within the lungs.…”
Section: Introductionmentioning
confidence: 99%